PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SD NEGERI 003 PERANAP - R. Syahputri Englia; Damhuri Daud; Jesi Alexander Alim (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : The background of this research is still low learning outcomes IPA SD Negeri 003 Peranap with an average of 58.00 since the learning is centered on the teacher and the student received less encouragement to develop their thinking skills so that learning outcomes are still low. The purpose of this research is to improve learning outcomes Elementary School School class IV IPA SD Negeri 003 Peranap by applying cooperative learning model jigsaw. This research was conducted by the method of action research. The subjects were School class IV grade students of SD Negeri 003 Peranap the number of students 25 people, consisting of 12 men and 13 women. This research instrument covers the syllabus, Learning Implementation Plan. Student Worksheet. Data analysis technique in this research is the activity of the teacher and student activity. The results showed an increase in learning outcomes of prior actions given cycle first and second cycle with an average of 58.00 class increased in the first cycle to 65.00 and the second cycle average of 47.00 class. The activities of teachers of the first cycle increased from the first meeting with an average of 57.50% to 75%, while at a meeting of the second cycle of meetings to thirth increased by an average of 85.00% to 87.50%. For student activity based on the results of the study an increase in activity of students in each of the learning process. Based on the results of this study concluded that the application of jigsaw cooperative learning model can improve learning outcomes IPA Elementary School class IV grade students SD Negeri 003 Peranap.Keywords: Cooperative Learning Model Jigsaw, Learning Outcomes IPA